UPAYA MENINGKATKAN KEMAMPUAN PENGUASAAN KOSAKATA BAHASA INGGRIS MELALUI METODE TOTALLY PHYSICAL RESPONSE (TPR) BAGI ANAK AUTISME (SINGLE SUBJECT RESEARCH DI KELAS IV SLB YPPA PADANG) - Nabila - Ulmi (Jurnal Penelitian Pendidikan Khusus, 2013)
The research was motivated by the problems of student with autism in the class IV SLB YPPA Padang, which he likes English lessons but when given the test about translated from English to Indonesia vocabulary form, which vocabulary he had learned, only a few he are able to know. This shows that child had problem to remembering English vocabulary he was taught. Therefore, the researchers chose the method totally physical response (TPR) that promotes physical activity in their implementation supported by the theory of John Dewey who said that if the students were asked to do something and report it, they will remember 90%. The purpose of this study was to see the impact of the use of totally physical response (TPR) on the development of English vocabulary skills of children and also to assist the child in overcoming the problem. This type of research is experimental research that single subject research (SSR) with A-B research design is to see the development of the child before the given treatment (baseline) in this study performed a total of 6 times after the meeting and were given treatment (intervention) performed 10 sessions. With target observed behavior is showing, speaking, writing, and translating the English vocabulary. The results of the analysis of the data showed that during the study period of 16 days appears the ability of vocabulary development in children from the baseline that only stabilize at 5 vocabulary and steady climb to 30 vocabulary that can be shown, described, written and interpreted in the intervention condition. It is proved giving totally physical methods have a positive response to the development of English vocabulary for children with autism in the class IV SLB YPPA Padang. From these results it can be concluded that administration totally physical response methods succeed improve English vocabulary skills for children with autisme.